Career Success, Participation and Representation of Women Academic Lecturers as Leaders in an Indonesian Tertiary Institution - Harahap, Hamida Syari; Yasya, Wichitra; Saimima, Ika Dewi Sartika (International Journal of Educational Research & Social Sciences, 2022)
The role of women in academic and structural positions in tertiary institutions is an important part of achieving gender equality, particularly in the educational sphere. The purpose of this research is to investigate the perceptions of women lecturers’ career success, participation, and representation, and to determine the factors that impede them or serve as barriers for women’s career success, participation, and representation in tertiary institutions. The research used a mixed methods approach, namely quantitative surveys that were analyzed using descriptive statistics, while qualitative data and descriptive statistical results were used to carry out model gender analysis of Sara H. Longwee’s "Women's Capability Framework," which emphasizes the importance of development for women. Respondents were selected from Bhayangkara Jakarta Raya University, a private university based in Jakarta, Indonesia. Results show that women perceived that their career success, participation, and representation in tertiary institutions were adequate. On the other hand, the barriers that impede the women’s career success, participation, and representation in tertiary institutions were both internal and external barriers, with internal barriers such as domestic affairs, psychological and emotional, ego and arrogance, and time management, playing a bigger role as impediments. Hence, it is recommended that tertiary institutions in Indonesia develop and enforce firm gender mainstreaming policies to support women in the workplace to overcome these barriers that hinder their career success, participation and representation.